Cover Image, Volume 25, Issue 6. (20th December 2018) - Safley, Susan A.; Kenyon, Norma S.; Berman, Dora M.; Barber, Graham F.; Willman, Melissa; Duncanson, Stephanie; Iwakoshi, Neal; Holdcraft, Robert; Gazda, Lawrence; Thompson, Peter; Badell, I. Raul; Sambanis, Athanassios; et al.
Abstract : The cover image is based on the Original Article Microencapsulated adult porcine islets transplanted intraperitoneally in streptozotocin‐diabetic non‐human primates by Susan A. Safley et al., DOI:10.1111/xen.12450